The role of tortuous configuration of coronary arteries in the development of clinical manifestations of ischemic heart disease - Y. Lebedieva; M. Grusha (Ukrainian Journal of Cardiovascular Surgery, 2018)
In the article we consider the role of tortuous configuration of coronary arteries (CA) in the occurrence of clinical manifestations of ischemic heart disease (IHD) in patients without any angiographic signs of atherosclerotic lesions of the vascular wall and with varying degrees of coronary stenosis. The results of general clinical, electrocardiographic and stress vector-echocardiographic examination of such patients are presented. Evidences of the importance of tortuous configuration of CA in the development of clinical manifestations of myocardial ischemia in case of absence and presence of angiographic signs of hemodynamically significant coronary atherosclerosis is presented. The role of tortuosity of CA in the coronary hemodynamics violation, reducing the functional reserves of the heart muscle and the occurrence of clinical manifestations of myocardial ischemia is demonstrated, which must be taken into account in early diagnosis of various forms of IHD.